Terapia moderna de la cetoacidosis diabética. Minidosis de insulina - Sánchez Gonzales , José D. (1979)
The conventional high dose insulin treatment of the diabetic ketoacidosis is often accompanied by complications such as hypokalemia and hypoglycemia, apart from the difficulty of a rapid restoration of the normal blood glucose values. Therefore low dose insulin treatment has been recommended in order to obtain physiological blood insulin concentrations as well as to avoid the above mentioned complications. The experiencia with this treatment schedule is reported in the present comunication.  From August 1978 to June 1979, 7 ketoacidotic episodes in 6 male patients were treated. Their ages varied from 13 to 42 years (mean 26.6); 3 patients were first diagnosed during ketoacidosis coma. The patients were unconscious, dehydrated, tachycardia, polypnea, acidosis, bicarbonate less than 10 mEq/l was present in three of them; three patients had acute renal insufficiency; one patients had a hypokalemia of 2.2 mEq/l; initial blood glucose values ranged from 350 to 707 mg/dl (mean 538.5, mg/dl).  Once ketoacidotic imbalance was diagnosed treatment was started with intramuscular regular insulin 5 lU per hour. Only one patients recived regular insulin 5 lU per hour as a continuous intravenous infusion, which is discussed separately. When blood glucose fell below 250 mg/dl, normal saline solution was changed to 5 percent glucose and insulin administered subcutaneously. Potassium chloride was given at a rate of less than 20 mEq/hr, beginning with the second hour of treatment. Sodium bicarbonate was infused only to patients having serum bicarbonato less than 10 mEq/l; antibiotics were also given.  Under this treatment schedule blood glucose fell to 250 mg/dl in 3 to 13 hours (x=7.6 hr). Ketone bodies diminished in 28 hours. In order to lower blood glucose below 250 mg/dl, 10 to 70 lU (x=38.3 lU) insulin was required. During the first 24 hours 45 to 110 lU (x=70 lU) insulin was needed; and 40 to 215 lU (x=89 lU) insulin was neccesary to restore conciousness.  During the first 6 hours and 24 hours, 1 to 3 liters (x=2 l) and 3 to 7.6 (x=5.2 l) were respectively employed: about 84 mEq/day potasium chloride were administered. The following antibiotic were used; cloramphenicol, genramicin, ampicillin or cefalosphorin.  The patient treated with a intravenous insulin infusion had developed ketoacidosis after a surgical procedure in which neither glucose nor insulin had been supplied.  Onlye one patient died. He had recovered from coma and had begun oral food intake, but a severe general infection of unknown etiology caused the death. All other patients recovered completely without any hypoglycaemic or hypokalemic complications.  The results presented confirm that low dose insulin schedule is a simple, safe, effective and easy method to treat diabetic ketoacidosis, to be employed even in institutions with scanty facilities.